Sistem Perencanaan Pembangunan Terintegrasi Melalui Penerapan E-Planning (Studi Kasus pada Bappeda dan Litbang Kabupaten Gianyar) - Juniawan, Wayan Dedy (Jurnal Ilmiah Administrasi Publik, 2019)
The medium-term planning arrangements in Gianyar Regency Year 2018-2023 have adopted the integrated development planning system Geyer (2006: 1) whicheach phase corresponds to the stages in the Regulation of the Minister of Home Affairs Number 86 of 2017. E-Planning plays a role in phase 0 (preparation) in collecting development data and information, phase 2 (strategy) during the submitting and verification of proposals in the development planning deliberations of the Regional Medium-Term Development Plan and phase 4 (integration) that is integrating the mission, goals, objectives, up to the regional program with the Regional Government Organization. This study aims to analyze the integrated development planning system through the implementation of e-planning in Gianyar Regency. This type of descriptive research with a qualitative approach was used in this study. This study also analyzes and describes the supporting and inhibiting factors that seem to be technical factors (ICT infrastructure, security, output and system features, SOPs, and technical training) and social/organization factors (commitment of leadership, work culture, communication and HR of implementing).